A boosting approach to forecasting the volatility of gold-price fluctuations under flexible loss. (March 2016) - Pierdzioch, Christian; Risse, Marian; Rohloff, Sebastian
Abstract: We use a boosting approach to study the time-varying out-of-sample informational content of various financial and macroeconomic variables for forecasting the volatility of gold-price fluctuations. We use an out-of-sample R 2 statistic to evaluate forecasts as a function of the shape of a forecaster's loss function. We show that, when compared to an autoregressive benchmark forecast, those forecasters tend to benefit from using predictions implied by the boosting approach who encounter a larger loss when underestimating rather than overestimating the future volatility of gold-price fluctuations. We use a simulation experiment to study the significance of this benefit. Abstract : Highlights: We use a boosting approach to forecast the volatility of gold-price fluctuations. We use different asymmetric loss functions to evaluate forecasts. Forecasters benefit from forecasts when underestimation is costlier than overestimation. We use simulations to assess the significance of benefits.